The snake fauna of the most threatened region of the Atlantic Forest: natural history, distribution, species richness and a complement to the Atlas of Brazilian Snakes - Filho, Gentil Alves; Marco Freitas; Washington Luiz; Geraldo Jorge Barbosa; Thais Barreto Guedes; Frederico Gustavo Rodrigues França (Ethnobiology and Conservation, 2021)
The Atlantic Forest is one of the richest tropical forests in the world, with a high endemism rate of vertebrates, including several snakes. The snake fauna of the Atlantic Forest is rich and complex, presenting differences in fauna composition along its extension. The existence of at least four endemism centers along this forest is well documented and supported by data of vertebrates, invertebrates and plants. The Pernambuco Endemism Center (PEC) is the most septentrional region of the Atlantic Forest, and it contacts areas with transitional forests and arid landscapes (Caatinga) which along with altitudinal variation enable a unique snake fauna for this region. In this study we provide: (i) an updated list of species, detailed information about natural history, as well as a detailed geographic distribution for all species recorded in the PEC; (ii) a comparison between the snake fauna of the PEC with other regions of the Atlantic Forest. The snake fauna of the PEC is composed by 86 species of 8 families. The results showed that most of the species recorded in the PEC are distributed close to the coast, probably due to the proximity of the research centers, but also due to the present distribution of the remnants close to the coast. The forest remnants in the highlands (Brejos de Altitude) harbors a high diversity of species with high similarity with the coastal forests. We found a strong separation between the snake fauna of assemblages located in southwestern and northeastern Brazil, indicating clear characteristics of the snake fauna of the PEC.